Hepatoprotective Effect of Cleome Viscosa L. Seeds in Paracetamol - Mobiya, Ashok Kumar (International Journal of Pharmaceutical & Biological Archive, 2010)
In present study, Hepatoprotective activity of the ethanolic extract of Cleome Viscosa L. seeds was studied on paracetamol treated albino rats. The hepatoprotective effect was evaluated on the basis of liver function parameters viz. serum total bilirubin, total protein, alanine transaminase, aspartate transaminase and alkaline phosphatase activities. Treatment with Cleome Viscosa L. seeds extract had shown significant hepatoprotective effect also supported by histopathological studies on liver, the result were in comparison with the standard drug silymarin.